Formas de aplicação de fontes de cálcio, magnésio e enxofre no cultivo do milho em condições controladas - Siqueira, Thiago Prudente (2018)
The application of correctives in a no-tillage system has often been ineffective in correcting soil acidity and in the supply of calcium and magnesium to the plants, but the adequate mineral nutrition of the crops, through the implementation of rational soil correction programs and fertilization, are indispensable for the sustainability and success of the system. The objective of this study was to evaluate the agronomic efficiency of two sources of correctives, one containing 60% CaO and 30% MgO and another 15.6% elemental sulfur and 56.21% CaO and 24.02% MgO, in the corn crop, in two types of soil with straw, evaluating different applications. The first chapter had the purpose of, from a bibliographical review, to discuss the management and the fertilization of the soil in no-tillage system in the Cerrado. The following chapters consisted of two distinct experiments (biological tests) in which the sources of correctives were evaluated in two soils with different textures and distinct eras, being a sandy and another clayey, classified as a Neossolo Quartzarênico órtico típico and Latossolo Vermelho distrófico típico, respectively, in a greenhouse belonging to the Universidade Federal de Uberlândia. 20 kg vases and the DKB390 VT PRO maize variety were used. The experimental design was completely randomized, with three replications. The treatments consisted of three doses (150, 300 and 450 kg ha-1), in two modes of application: under and over straw, with two additional ones: without straw (control 1) and straw (control 2) both without application of the corrective sources. For the vegetal analysis, a double factorial arrangement with two additional (3 x 2 + 2) was used and for the chemical analysis of the soil, a triple subdivide factorial arrangement (3 x 2 x 5) was carried out, where five depths were evaluated (0-2, 2-4, 4-6, 6-8 and 8-12 cm). During the whole experiment a cumulative 250 mm rain was simulated. The following were evaluated: stem diameter; plant height; mass of shoot dry matter; calcium, magnesium and foliar sulfur contents and soil chemical parameters. The statistical assumptions of the obtained data were tested, which were submitted to analysis of variance by Tukey test and Dunnett test, both 0.05 of significance. Significant data for the quantitative factor (doses) were submitted to regression analysis. The application in sandy soil of the corrector containing 60% CaO and 30% MgO, under greenhouse conditions, changes the shoot dry matter mass, stem diameter and height of maize plants, as well as the active and potential acidity and the calcium, magnesium and aluminum contents in the soil, for both soils. The corrective application of 15.6% elemental sulfur and 56.21% and 24.02% CaO and MgO, respectively, under greenhouse conditions, changes the sulfur content in the aerial part of the corn grown in sandy soil and the magnesium content in the aerial part of maize grown in clay soil. The application of the corrective in both soils changes the active and potential acidity and the levels of calcium, magnesium, sulfur and aluminum in the soil. In general, the application of the corrective under the straw provided superior results, to the detriment of the application on the latter.